2005
DOI: 10.1002/bse.434
|View full text |Cite
|
Sign up to set email alerts
|

Caveat emptor - let the buyer beware! environmental labelling and the limitations of ‘green’ consumerism

Abstract: In recent years, the idea of 'green' or 'political' consumers expressing their political beliefs in everyday life has been widely embraced. Eager to satisfy the needs of this new market segment, firms have allocated substantial resources to environmental management, social accountability, corporate citizenship, occupational health and safety etc. During the 1990s, the industrialized world also witnessed a growing number of environmental labels, expected to guide the political consumers in their shopping decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
0
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(148 citation statements)
references
References 24 publications
(37 reference statements)
5
131
0
12
Order By: Relevance
“…However, after exploring consumers' perceptions of different types of labelling and their knowledge it became apparent that environmental knowledge alone is not enough to enable consumers to understand the "labelling-scape". This corresponds with previous studies that stressed the weakness of the link between environmental knowledge and behaviour [42,50]. This research found that consumers decode various sustainability claims through environmental knowledge (abstract and concrete), political, branding, and labelling knowledge.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, after exploring consumers' perceptions of different types of labelling and their knowledge it became apparent that environmental knowledge alone is not enough to enable consumers to understand the "labelling-scape". This corresponds with previous studies that stressed the weakness of the link between environmental knowledge and behaviour [42,50]. This research found that consumers decode various sustainability claims through environmental knowledge (abstract and concrete), political, branding, and labelling knowledge.…”
Section: Discussionsupporting
confidence: 91%
“…In the marketing literature knowledge of labels has received attention [5,[49][50][51]. Past research suggested that consumers prefer products that have a familiar seal on their packaging [52].…”
Section: Labelling Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…The use of such heuristics is particularly important when understanding how users react to information on the energy consumption and environmental impact of a product. This might well explain why in the field of sustainable consumption attempts to increase consumer knowledge through provision of information have shown little impact on behavior (Davies et al 2002;Gardner and Stern 2002;Pedersen and Neergaard 2006;Moisander 2007). Moreover, if products differ on several dimensions such as energy efficiency, pollution, durability, and price, it is unlikely that the decision maker will integrate all of these into his choice.…”
Section: Limits In Information Processingmentioning
confidence: 99%
“…Publicly available information on energy issues is reported as being in surprisingly short supply and some of it is conflicting (Brand, 1997;Blowfield et al, 2001;Kuisma, 2001;Lybäck, 2002;Neergaard & Pedersen, 2006). For many people, energy saving automatically conjures up the idea of fewer comforts and a lower quality of life (Aho et al, 2006).…”
Section: Lowmentioning
confidence: 99%